2005
DOI: 10.1177/0010414004273928
|View full text |Cite
|
Sign up to set email alerts
|

Why Some Anti-Immigrant Parties Fail and Others Succeed

Abstract: Over the past two decades, some anti-immigrant parties have managed to gain substantial electoral support in various European countries, most notably Austria (FPÖ) and Flanders (Vlaams Blok). However, in other countries the success of such parties has either been insignificant or did not last. We argue that the most popular models of support for antiimmigrant parties -the socio-structural model and the protest vote model -cannot explain the huge differences in support for these parties. Instead, we develop a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(72 citation statements)
references
References 35 publications
3
66
0
3
Order By: Relevance
“…Implicit in the quarrel of memories over colonial Algeria are conflicting visions of France today. Unlike those who defend equal rights for all in a system that makes ethnic and religious identity irrelevant for full citizenship, those with nostalgia for empire desire a strong state, an ethnic definition of nationality and citizenship and a hierarchical separation of different racial groups (Stora 1999;Blanche 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Implicit in the quarrel of memories over colonial Algeria are conflicting visions of France today. Unlike those who defend equal rights for all in a system that makes ethnic and religious identity irrelevant for full citizenship, those with nostalgia for empire desire a strong state, an ethnic definition of nationality and citizenship and a hierarchical separation of different racial groups (Stora 1999;Blanche 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the realisation of inclinations to populist alternatives depends on many factors, not alone the supply of potent populist actors. As Van der Brug, Fennema and Tillie (2005) emphasised, a vote aimed at punishing political elites is qualitatively different from a regime protest vote, one that aims to change the political system and main political ideologies.…”
Section: Discussionmentioning
confidence: 99%
“…A potential demand is a necessary but not a sufficient condition for the success of populists (Van der Brug, Fennema and Tillie, 2005) because the other half rests on supply-side explanations, which deal with the internal dynamics of populist parties, the role of the populist leader, as well as the broader political opportunity structure (a complex mix of institutional, political and cultural factors; Mudde, 2007;Norris, 2005). In that regard, demand-side analysis tries to "explain why and which people constitute the potential electorate of populist" parties (Mudde, 2007: 230).…”
Section: Populism and Democracy -A Complex Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, various scholars have also shown that Euroscepticism is strongly related to voting for PRR parties (Arzheimer 2009;Ivarsflaten 2005;Lubbers and Scheepers 2007;Van der Brug et al 2005;Werts et al 2012). Many mainstream parties offer moderate messages when it comes to their positions on European integration.…”
Section: Who Votes For the Prr And Why?mentioning
confidence: 99%